Psyllium husk gel used as an alternative and more sustainable scalding technology for wheat bread quality improvement and acrylamide reduction - Bartkiene, Elena; Kungiene, Giedre; Starkute, Vytaute; Klupsaite, Dovile; Zokaityte, Egle; Cernauskas, Darius; Kamarauskiene, Egle; Özogul, Fatih; Rocha, João Miguel (Frontiers in Nutrition, 2023)
This study aimed at evaluating the influence of different amounts (5, 10, 15, 20 and 25%) of psyllium husk gel (PHG) on wheat bread (WB) characteristics – chiefly, overall acceptability (OA), porosity, specific volume (v), mass loss after baking (ML), shape retention coefficient, crust and crumb colour coordinates, bread crumb hardness during storage, saccharides content and acrylamide (AA) concentration. PHG was prepared by mixing 100 g of psyllium husks powder with 800 mL of warm water. It was established that the amount of psyllium husk gel is a significant factor on dough redness (a*) (p<0.001). Moderate positive correlation (r) was found between acrylamide content in wheat bread and maltose concentration in dough (r=0.567). The psyllium husk gel increased the overall acceptability and specific volume of wheat bread. Wheat bread porosity showed moderate positive correlation with mass loss after baking (r=0.567) and strong positive correlation with texture hardness (r=0.664). Lower acrylamide content was obtained in wheat bread prepared with 5, 10, 15, 20 and 25% of psyllium husk gel (1.53, 2.34, 3.80, 2.69 and 3.62 times lower than the control wheat bread, respectively). Acrylamide content showed a strong positive correlation with porosity of wheat bread (r=0.672), with crust brightness (L*) and yellowness/blueness (b*) coordinates, as well as with crumb brightness, redness and yellowness coordinates. Overall, psyllium husk gel hydrocolloids reduced acrylamide formation in wheat bread and can be recommended towards the quality improvement of wheat bread.